PENGARUH FLEXING DAN GAYA HIDUP MEWAH TERHADAP BRAND AWARENESS MELALUI PERSONAL BRANDING - Alika Rahmah; Zeffanya Raphael Wijaya (PT Naureen Digital Education, 2026)
This study analyzes the influence of flexing and luxurious lifestyles on brand awareness through personal branding on the TikTok platform, using Shella Saukia as a case study. A quantitative method with a causal design was used, involving 100 active TikTok users who were familiar with the @shellasaukia account. Data analysis used path analysis with SPSS and AMOS. The results showed that flexing has no significant effect on personal branding (t=1.719; p=0.086), while luxurious lifestyle has a significant effect (t=3.454; p=0.000). Personal branding has a significant effect on brand awareness (t=9.248; p=0.000). Simultaneously, flexing and luxurious lifestyle have significant effects on personal branding (F=49.87; R²=0.507) and on Brand awareness (F=59.04; R²=0.476). Personal branding acts as a partial mediator with an indirect effect of luxurious lifestyle of 0.269. These findings contribute to digital communication strategies on social media.